Game Portal Virtual Tugu Pahlawan Dengan Mobile Device Menggunakan Augmented Reality - Muhammad Hafidh Al-Ghifari; Maulana Rizqi (Institut Seni Indonesia Yogyakarta, 2020)
The development of virtual game applications has become an attraction for some people. More specifically, Augmented Reality technology can introduce directly how the atmosphere in a certain location or place, therefore, in this study we tried to create applications that combine the real world with the virtual world. By using the Markerless Augmented Reality method which allows users to use the application anywhere and is not limited by markers. With the Augmented Reality application it also allows users to feel the atmosphere directly in the virtual world. For example, like the Tugu Pahlawan Monument in Surabaya, Augmented Reality technology can be utilized by introducing directly to the public about historical buildings in Surabaya, so that people who have never been there or who have been there by using the Augmented Reality application can immediately feel as if they are located at Tugu Pahlawan, and with a virtual portal it will connect the user’s location with the Tugu Pahlawan Monument and only use a mobile device.